A colorectal cancer susceptibility new variant at 4q26 in the Spanish population identified by genome-wide association analysis. - Luis M Real (Public Library of Science (PLoS), 2014)
Background Non-hereditary colorectal cancer (CRC) is a complex disorder resulting from the combination of genetic and non-genetic factors. Genome-wide association studies (GWAS) are useful for identifying such genetic susceptibility factors. However, the single loci so far associated with CRC only represent a fraction of the genetic risk for CRC development in the general population. Therefore, many other genetic risk variants alone and in combination must still remain to be discovered. The aim of this work was to search for genetic risk factors for CRC, by performing single-locus and two-locus GWAS in the Spanish population. Results A total of 801 controls and 500 CRC cases were included in the discovery GWAS dataset. 77 single nucleotide polymorphisms (SNP)s from single-locus and 243 SNPs from two-locus association analyses were selected for replication in 423 additional CRC cases and 1382 controls. In the meta-analysis, one SNP, rs3987 at 4q26, reached GWAS significant p-value (p = 4.02×10(-8)), and one SNP pair, rs1100508 CG and rs8111948 AA, showed a trend for two-locus association (p = 4.35×10(-11)). Additionally, our GWAS confirmed the previously reported association with CRC of five SNPs located at 3q36.2 (rs10936599), 8q24 (rs10505477), 8q24.21(rs6983267), 11q13.4 (rs3824999) and 14q22.2 (rs4444235). Conclusions Our GWAS for CRC patients from Spain confirmed some previously reported associations for CRC and yielded a novel candidate risk SNP, located at 4q26. Epistasis analyses also yielded several novel candidate susceptibility pairs that need to be validated in independent analyses.